The Production of a Sense of Place among Jewish Immigrants in Mandatory Palestine - Zeev Shavit (Diasporas: Circulations, Migrations, Histoire)
The article discusses the production of a sense of place among Zionist immigrants who came to Palestine at the first three decades of the 20th century. This was manifested through various practices clustered under the name «Knowledge of the Land». The article analyzes the symbolic meanings which helped turning Palestine into a concrete place for these immigrants.